2012
DOI: 10.3233/jad-2012-120298
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol and Synaptic Compensatory Mechanisms in Alzheimer's Disease Mice Brain During Aging

Abstract: Research into the development of Alzheimer's disease (AD) provides increasing evidence that vascular risk factors, including high serum cholesterol, might influence the progression of cognitive impairment and neural degeneration. In this study, we investigated the effects of high dietary cholesterol intake and the cholesterol-lowering liver X receptor-agonist T0901317 on capillary density, amyloid-β deposition, and presynaptic boutons in the hippocampus of adult (8 months) and aged (15 months) AβPPswe-PS1dE9 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 103 publications
2
21
0
Order By: Relevance
“…In cell culture systems, the production of Aβ is modulated by cholesterol, and studies using animal models have consistently demonstrated that hypercholesterolemia is associated with an increased deposition of cerebral Aβ peptides [24]. The link between cholesterol levels and AD is also amplified by the finding that many proteins involved in cholesterol metabolism, such as liver X receptor (LXR), have been shown to be associated with late onset AD [7, 25]. One study indicated that the application of a cholesterol-reducing LXR agonist improved the quantity of presynaptic boutons [7], regulated neuroinflammation, and decreased Aβ accumulation [26].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In cell culture systems, the production of Aβ is modulated by cholesterol, and studies using animal models have consistently demonstrated that hypercholesterolemia is associated with an increased deposition of cerebral Aβ peptides [24]. The link between cholesterol levels and AD is also amplified by the finding that many proteins involved in cholesterol metabolism, such as liver X receptor (LXR), have been shown to be associated with late onset AD [7, 25]. One study indicated that the application of a cholesterol-reducing LXR agonist improved the quantity of presynaptic boutons [7], regulated neuroinflammation, and decreased Aβ accumulation [26].…”
Section: Discussionmentioning
confidence: 99%
“…The link between cholesterol levels and AD is also amplified by the finding that many proteins involved in cholesterol metabolism, such as liver X receptor (LXR), have been shown to be associated with late onset AD [7, 25]. One study indicated that the application of a cholesterol-reducing LXR agonist improved the quantity of presynaptic boutons [7], regulated neuroinflammation, and decreased Aβ accumulation [26]. The administration of statins has also been demonstrated to protect against AD [27, 28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The amyloidogenic pathway is predominantly associated with lipid rafts, whereas the non-amyloidogenic pathway is correlated with non-lipid rafts [119,120]. Accumulating evidence suggests a key role for a disturbed CNS cholesterol homeostasis in the development and progression of AD [121][122][123][124][125][126][127]. In this section, we elaborate on the impact of sterol metabolism on the development and progression of AD, and discuss how phytosterols may impact AD pathology.…”
Section: Phytosterols In Alzheimer's Diseasementioning
confidence: 97%
“…Immunohistochemistry was performed using standard freefloating labeling procedures, using the protocol described by Jansen et al (2012Jansen et al ( , 2014 and Janssen et al (2015). For DCX, polyclonal goat anti-doublecortin (1:4000; Santa Cruz Biotechnology Inc., Santa Cruz, CA, USA) was used as a primary antibody to assess neurogenesis.…”
Section: Immunohistochemistrymentioning
confidence: 99%